2011
DOI: 10.1186/1750-1326-6-83
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of striatal transcriptome in mice overexpressing human wild-type alpha-synuclein supports synaptic dysfunction and suggests mechanisms of neuroprotection for striatal neurons

Abstract: BackgroundAlpha synuclein (SNCA) has been linked to neurodegenerative diseases (synucleinopathies) that include Parkinson's disease (PD). Although the primary neurodegeneration in PD involves nigrostriatal dopaminergic neurons, more extensive yet regionally selective neurodegeneration is observed in other synucleinopathies. Furthermore, SNCA is ubiquitously expressed in neurons and numerous neuronal systems are dysfunctional in PD. Therefore it is of interest to understand how overexpression of SNCA affects ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 75 publications
2
25
0
Order By: Relevance
“…Alpha-synuclein overexpression disrupts transcription in the striatum of young Thy1-aSyn mice (Cabeza-Arvelaiz et al, 2011) and previous studies of substantia nigra pars compacta tissue in mice overexpressing alpha-synuclein under the tyrosine hydroxylase promoter showed extensive differences in genes involved in transcription or translation, as well as signal transduction (Miller et al, 2007). In mice over-expressing alpha-synuclein under the PDGF promoter (Yacoubian et al, 2008) changes were observed in a small number of genes at 3 months of age with increased alterations at 9 months.…”
Section: Resultsmentioning
confidence: 76%
“…Alpha-synuclein overexpression disrupts transcription in the striatum of young Thy1-aSyn mice (Cabeza-Arvelaiz et al, 2011) and previous studies of substantia nigra pars compacta tissue in mice overexpressing alpha-synuclein under the tyrosine hydroxylase promoter showed extensive differences in genes involved in transcription or translation, as well as signal transduction (Miller et al, 2007). In mice over-expressing alpha-synuclein under the PDGF promoter (Yacoubian et al, 2008) changes were observed in a small number of genes at 3 months of age with increased alterations at 9 months.…”
Section: Resultsmentioning
confidence: 76%
“…By preventing the formation of amyloid beta fibrils, TTR may also play a neuroprotective role in degenerative diseases such as Alzheimer disease [29]. In connection with PD, Ttr is upregulated at a pre-manifest stage in the SNc of MPTP-treated monkeys [39] and in the striatum of mice overexpressing human α-synuclein gene [40], suggesting a role in compensatory processes. Ttr is also upregulated in response to nicotine [41], which, according to epidemiological data and studies in animal models, may protect against PD [42].…”
Section: Discussionmentioning
confidence: 99%
“…A broader investigation concerning a-synuclein was performed in silico; mice overexpressing human wild-type SNCA were used to perform a transcriptome analysis of the striatal brain region [171]. The expression of many genes implicated in apoptosis, cell cycle progression, neurogenesis and synaptic function were impaired, demonstrating that indeed a-synuclein is involved in many different cell processes that, when deregulated due to differential SNCA expression, may influence neurogenesis.…”
Section: Snca (Park1/park4)mentioning
confidence: 99%